Cumulative sum analysis of the learning curve for video-assisted minilaparotomy donor nephrectomy in healthy kidney donors. Issue 17 (April 2018) - Park, Jee Soo; Ahn, Hyun Kyu; Na, Joonchae; Lee, Hyung Ho; Yoon, Young Eun; Yoon, Min Gee; Han, Woong Kyu
Abstract : Abstract: Video-assisted minilaparotomy surgery (VAMS) is a hybrid of open and laparoscopic surgical techniques, so has advantages of both approaches. Here, we examined the learning curve for this procedure. We retrospectively evaluated 50 consecutive patients who underwent VAMS donor nephrectomy performed by a single surgeon (YEY) between March 2015 and March 2016. The learning curve was evaluated using the cumulative sum (CUSUM) method. Measures of surgical performance included total operation time, warm ischemic time, and estimated blood loss. The mean patient age, body mass index, and body surface area were 43.5 years, 23.8 kg/m 2, and 1.7 m 2, respectively. The mean operation time and warm ischemic time were 160.0 minutes and 124.4 seconds. The learning curve of total operation time was best modeled as a second-order polynomial with equation CUSUM OT (minutes) = –0.3802 × case number 2  + 20.315 × case number – 41.333 ( R 2  = 0.7707). The curve included 3 unique phases: phase 1 (the initial 17 cases), which is the initial learning curve; phase 2 (the middle 23 cases), expert competence, and phase 3 (the subsequent cases), mastery. In terms of warm ischemic time and estimated blood loss, the initial learning was achieved after 16 cases and after 9 to 10 cases, one could achieve competency. The VAMS donor nephrectomy learning curve is shorter than for laparoscopic or robotic hand-assisted donor nephrectomy. Surgeons can become familiar with the procedure and perform it without complications after approximately 16 to 17 operations.